A rare case presentation of top of basilar artery syndrome - Sriharsha, Tirumalasetty; Gopal, Sava Nandha; A., Arun Kumar; V., Vikrannth; Raghavan, Vinod; Rajendran, Kannan (International Journal of Advances in Medicine, 2023)
Top of basilar syndrome occurs due to the thrombotic occlusion of basilar artery. It is very rare in occurrence and constitutes about 1% of all strokes. Clinical manifestations commonly may have the hallmarks of basilar artery occlusion that include dysarthria, visual, oculomotor and behavioural abnormalities with or without significant motor dysfunction and non-specific symptoms like vertigo and headache. Here we report a case of 60year old male who presented with decreased responsiveness and slurring of speech since 2 days and history of vomiting since one day. Neurological examination revealed normal higher mental functions with MMSE score of 28/30, horizontal nystagmus was present, other cranial nerve examination was normal, tone was increased in all the four limbs, Power was 4/5 in all the 4 limbs and Plantar was mute bilaterally. Patient condition deteriorated later and on further evaluation patient was found to have Basilar Artery Occlusion.